Influencing Factors Interest of Young Farmers (Millennials) in The Agricultural Sector in Lebakwangi District, Kuningan Regency - Fauzi, Muhammad Salman Alfarisi; Rahman, Fakhri Nur; Farhan, Muhammad; Faqih, Achmad; Fauzi, Nurul Arifah (International Journal Labs, 2025)
Kuningan Regency is an area that has abundant natural resource potential, both the wealth of water resources and the potential for agricultural land that is still productive (fertile). Lebakwangi District is one of the areas of Kuningan Regency that has significant agricultural potential. However, the interest of the younger generation in the agricultural sector is still considered low. This study aims to examine the impact of internal factors (motivation and personality) and external factors (family economic conditions and government policies) on the interest of millennial farmers in Lebakwangi District. This research was carried out in Lebakwangi District, Kuningan Regency. The research was carried out from May to June 2025. The method used was a descriptive quantitative approach with a simple random sampling technique for 82 respondents, as well as multiple linear regression analysis using SPSS 27. The results showed that simultaneously these four factors had a significant effect on the interest of young farmers (R² = 0.538). Partially, motivation and personality have a significant influence, while family economic conditions and government policies have no significant effect individually. The results of this study show that strengthening internal factors is the main key in increasing the interest of the younger generation in agriculture. This research is expected to be the basis for formulating a strategy for the development of millennial farmers to maintain the sustainability of the agricultural sector in the region.